86.3k views
4 votes
What us 6+8(4w-7)-(2w+1)

User Taesha
by
4.7k points

2 Answers

2 votes

Answer:W=1.7

Step-by-step explanation: Simplifying

0 = 6 + 8(4w + -7) + -1(2w + 1)

Reorder the terms:

0 = 6 + 8(-7 + 4w) + -1(2w + 1)

0 = 6 + (-7 * 8 + 4w * 8) + -1(2w + 1)

0 = 6 + (-56 + 32w) + -1(2w + 1)

Reorder the terms:

0 = 6 + -56 + 32w + -1(1 + 2w)

0 = 6 + -56 + 32w + (1 * -1 + 2w * -1)

0 = 6 + -56 + 32w + (-1 + -2w)

Reorder the terms:

0 = 6 + -56 + -1 + 32w + -2w

Combine like terms: 6 + -56 = -50

0 = -50 + -1 + 32w + -2w

Combine like terms: -50 + -1 = -51

0 = -51 + 32w + -2w

Combine like terms: 32w + -2w = 30w

0 = -51 + 30w

Solving

0 = -51 + 30w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-30w' to each side of the equation.

0 + -30w = -51 + 30w + -30w

Remove the zero:

-30w = -51 + 30w + -30w

Combine like terms: 30w + -30w = 0

-30w = -51 + 0

-30w = -51

Divide each side by '-30'.

w = 1.7

Simplifying

w = 1.7

User Vijay Kumbhar
by
5.0k points
1 vote

Answer:

30w-51

Explanation:

6+8(4w-7)-(2w+1)

Distribute

6 + 32w-56 -2w-1

Combine like terms

32w-2w +6-56 -1

30w-51

User Gene Golovchinsky
by
5.4k points